A study of contemporary public land bank as an alternative approach to address land requirements of public housing programs in urban areas the case of Quezon City - Ramos, Angeline C.; Magnaye, Dina C.; Chaves, Carmeli Marie C.; Yap, David Leonides T. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2019)
The state of the housing program in the Philippines is in critical condition. There was a significant housing backlog of 5.7 millions units in 2017. The annual average supply is only 150,000 units. To close the gap, 723,579 houses should be built each year (HLURB 2018). The national and local governments have explored many strategies to address these problems but the housing backlog has failed to narrow down. One of its causes is land supply shortage. The study focused on contemporary public land bank practices and how these can contribute to reducing the gap between land supply and housing demand in urban areas. The main objective was to establish the potentials of a contemporary public land banking system. The study area was Quezon City, the epitome of an urban area with a well conceived shelter program for its low-income and informal settler families representing 28% of the city's households. It is currently facing a serious land supply shortage resulting from current procedures in its public land market system. These preferred mode of land acquisition of foreclosed properties takes years to process while the disposition of lands is also lengthy and tedious due to legal requirements. Modern land banking is a planning tool that can legally aid LGUs. In the case of Quezon City, the study explored the potential of land banking tools and recommends the formulation of a transparent data-based inventory system, policies for conduit transfer, inter-local transfer, in rem bulk foreclosure, branding of surplus properties, and quiet title actions in aid of land acquisition. The selection of these strategies is founded on the premise that the time and the operational costs of land acquisition will be trimmed down. Land banking, when intelligently strategized can be beneficial to both the land market system and the city's housing programs.
Thesis (M.A. Urban and Regional Planning)--University of the Philippines Diliman
Keywords: Housing -- Philippines -- Quezon City; Low-income housing -- Philippines -- Quezon City